N6-methyladenosine modification of viral RNA and its role during the recognition process of RIG-I-like receptors - Li, Huanan; Guo, Yang; Qi, Wenbao; Liao, Ming (Frontiers in Immunology, 2022)
N6‐methyladenosine (m6A) is the most abundant RNA chemical modification in eukaryotes, and it is also found in the viral RNAs of many viruses. In recent years, m6A RNA modification has been reported to function not only in the replication of numerous viruses, but also in the innate immune escape process. In this review, we summarize the viruses that contain m6A in their viral genomes or viral mRNAs and generalize the effects of m6A on the replication of different viruses. In addition, we also describe how m6A modification helps viral RNAs to escape from recognition by the exogenous RNA sensors, retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs), during viral invasion. Overall, the goal of our review is to summarize how m6A regulates viral replication and facilitates innate immune escape. Furthermore, we discuss the potential of m6A as a novel antiviral target.